Effect of Microwave Heating on the Dielectric Properties and Components of Iron-Fortified Milk - Xiao-shu Tang; Da-ming Fan; Feng Hang; Bo-wen Yan; Jian-xin Zhao; Hao Zhang (Journal of Food Quality)
With the iron-fortified milk as research object, this paper makes a research on the influence of iron on the dielectric properties and wave absorption properties and effect of nutritional components, such as casein and whey protein in milk, and thermostability in the process of microwave heating, and rapid heat transfer method in ferrous gluconate–milk and ferrous chloride–milk, respectively. The results show that the iron of ionic form has greater influence to convert microwave to heat energy and the effect of microwave absorption properties was greater for ferrous chloride than for ferrous gluconate at high concentration. The effect of different forms of iron on the composition of milk was different, and the composition of milk systems was more stable by microwave heating, but the rapid heat transfer method is superior in the aim of increasing the nutritional value of milk. The ferrous gluconate–milk system has a better thermal stability than ferrous chloride–milk system. From the aspect of dielectric induction, the paper discovers the response rules of iron and evaluates the microwave thermal safety of the traditional and the iron-fortified products by microwave heating.